Stimulasi Fission Pada Reproduksi Aseksual Teripang Holothuria atra - Muttaqin, Aklif Reza; Hartati, Retno; Wibowo, Edi (977-2407769)
The production of sea cucumber in the wild has declined, it is due to excessive use and arrests for cultivation without any effort. Sea cucumber are generally reproduce sexually and asexually. Sexual reproduction through spawning and gametogenesis while, asexual reproduction through fission. Fission is the process of splitting a part of the specimen anterior, middle and posterior to the cucumber. The third part will grow into a new individual after each able to regenerate the missing parts of the specimen. Fission on sea cucumber can be stimulated by binding on the body of sea cucumber. The research was conducted in April-July 2012 in Bandengan, Jepara in order to objectives determine the success rate of asexual reproduction and regeneration rate and survival rate in sea cucumber Holothuria atra fission yield. The method used was experimental research in the field. The results of this study indicate the success rate of asexual reproduction in the sea cucumber H. atra fission yield was higher in H. atra large groups with a fission plane. At this stage of the regeneration of the posterior H. atra large groups with a fission plane is the most rapid in the middle regenerate regenerate while the slowest. Highest survival rate found in H. atra large groups with a fission plane, especially in the posterior.. Totality, post stimulated sea cucumber by fission would processing fission, wound closing process, regeneration process will form a mouth and new anus.